The remembrance of malam berinai expressed through digital art / Dayang Intan Farahanies Almurid ... [et al.] - Almurid, Dayang Intan Farahanies; Umar, Nur Fatin; Mustafa, Muhammad Khalik; Saleh, Nasyirah; Abdul Karim, Khairi Asyraf (2022)
"MALAM BERINAI," also referred to as "henna night". Henna was a dried and powdered leaf of the Lawsonia inermis and is frequently used as a skin, hair, and nail color as well as a kind of body art. Particularly in Islamic and Hindu civilizations, the origin, which originated in India, has become a tradition. This custom is typically followed a few days before the solemnization or Malay wedding to foster closer ties among family members. The final moments of the subject before becoming someone's wife were depicted by the artist using digital art in adobe illustration 2020 that create for the AICAD Art Exhibition Virtual 2021 theme Tales of the Cities. This artwork was a real event that gave inspiring to the artist to illustrate her best friend to keep as a memory for her.